Rastreamento visual em crianças da educação infantil e ensino fundamental 1: acuidade visual, motilidade extrínseca ocular e acuidade estereoscópica - Quercia, Andressa Zanini Fantato [UNIFESP] (2019)
Objective: Screening programs for visual problems in childhood provide access for the child population to ophthalmological assessment and thus enable the detection of eye diseases and the prevention of visual impairment and blindness in childhood. The objective of this work was to analyze the results of visual acuity, extrinsic ocular motility and stereoscopic acuity of children in Early Childhood Education and Elementary School I evaluated in the Eye Health Promotion Program held at Escola Paulistinha de Educação. Methods: This cross-sectional, retrospective observational study was carried out based on the review of medical records of children attended from 1992 to 2017. Visual acuity (VA) data presented monocular far (cortical in the Snellen table or angular with optotype “E” of Snellen / Sjogren's “hand”), state of ocular extrinsic motility (MEO) and stereoscopic acuity (LA) were tabulated. Medical records without information on date of birth, visual acuity or state of extrinsic ocular motility were excluded. For data analysis, the AV values ​​obtained in decimal were converted into logMAR and the participants were grouped into three age groups (<6 years, ≤ 6 to 9 years and> 9 years). The level of statistical significance was considered as P≤0.05. Results: From the total of 1922 reviewed medical records, data from 1705 students (50.21% female) were included, ranging in age from 2 years and 5 months to 12 years and 2 months (mean = 5.16 ± 1.76 years). The VA presented in the eye with the best vision varied from 0.00 to 0.70 logMAR (mean = 0.03 ± 0.07 logMAR) and was better in children older than 9 years. The AE varied from 40 to 800 seconds of arc (mean 108 ± 160 seconds of arc) and was better in children from 6 years of age. Two hundred and thirty-six (13.84%) students had some degree of visual impairment (VA ≤0.16logMAR or 0.7) in one or both eyes. Alteration of the MEO was observed in 44 students (59.09% with manifest strabismus and 40.91% with intermittent strabismus), with manifest esotropia being present in 50% of the cases. Of the total of 1705 examined, 417 referrals were made to the eye service, mainly due to visual impairment. Conclusions: Visual and stereoscopic acuity were better in children from 6 years of age. The frequency of low vision in at least one eye was 13.84% and strabismus, 2.58%. In general, visual screening enabled early referral to ophthalmological assessment, positively impacting school learning and children's quality of life.